HUBUNGAN PENGETAHUAN DAN SIKAP IBU SERTA DUKUNGAN KELUARGA TERHADAP PEMANFAATAN PELAYANAN ANTENATAL - Ariyanti, Lilik; Nugroho P, Priyadi; Irene Kartasurya, Martha (Jurnal Farmasi (Journal of Pharmacy), 2017)
The high maternal mortality rate in Indonesia is related to the low result of the implementation of Ante Natal Care (ANC). The result of the programe in Godog reported is still for compared to the target decided ramely, first visit K1 reported was 68,75% and fourth visit K4 reported was 57,14%. This study aimed to determined the relationship of mother’s knowledge and attitude and family support to the utilization of antenatal services. Kind of this research was explanatory research with cross sectional desain. Data collection by structured quesioner interview. Sample of this study are 45 by using simple random sampling technique. Data analysis for relation test used Chi-Square with 5% significance level. Dependent variable was utilization of health services, and independent variable were knowledge, attitude and family support. The quesioner of knowledge, attitude and family support tested in validitas and reabilitas before. Respondent in Godog Village had a good knowledge (46,7%), positive attitude to antenatal services utilization (66,7%) and got family support (73,3%).The result showed that antenatal services utilization was about 75,6%. Knowledge (=0,001) and family support (=0,044) were significantly associated to antenatal services utilization. Others factor, attitude was not significantly associated. In conclusion that better knowledge and the presence family support could improve the antenatal services utilization.